Prevention of Recurrent Upper Respiratory Tract Infections in a Community of Cloistered Nuns Using a New Immunostimulating Bacterial Lysate - Tricarico, Davide; Varricchio, Attilio; D’Ambrosio, Salvatore; Ascione, Enrico; Motta, Gaetano (Arzneimittelforschung, 2004)
The aim of the present study was to evaluate the efficacy of the immunosti-mulating therapy with a new vaccine Is-migen® in preventing recurrent infections of the upper respiratory tract in subjects belonging to a community of cloistered nuns. This product is a lysate obtained by mechanical lysis of bacteria (MLBL) usually responsible of respiratory tract infections.A randomized, double-blind, parallel groups, placebo controlled clinical trial was carried out in 47 nuns (age range 25–80 years) living in a cloistered religious community, suffering from recurrent infections of the upper respiratory tract.The 47 patients were allocated by randomization to two groups:Group A – The 24 patients (mean age ± SD: 48.12 ± 14.25 years) of this group received one sublingual tablet of MLBL per day, for 10 consecutive days per month for 3 consecutive months (October, November and December 2001).Group B – The 23 patients (mean age ± SD: 49.04 ± 14.73 years) of this group received daily one sublingual tablet of taste masked placebo, for 10 consecutive days per month for 3 consecutive months (October, November and December 2001).At the end of the treatment period patients of both groups were followed up for further three months without any im-munostimulating treatment.Results: During and at the end of the treatment phase the number of respiratory infections (primary end-point) and their duration were statistically significantly lower in the MLBL group than in the placebo group. Moreover the administration of MLBL induced a marked reduction in the number of patients showing symptoms of infection in comparison to baseline and approximately 79 % of the patients showed an improvement of one or more of the evaluated symptoms.In the MLBL group a statistically significant increase of serum immunoglobulins (IgG +35 %; IgM +86 %; IgA +80 %) and salivary IgA (+ 110 %) was found, in comparison to baseline; on the contrary no significant differences were observed in the placebo group.The beneficial effects of MLBL found in the treatment period were maintained also in the three-month follow-up.No adverse events associated with the treatment were found in both group.The results of this study demonstrate that MLBL is an efficacious and safe therapeutic option for the treatment and prevention of recurrent upper respiratory tract infections and that its use is recommended in subjects with a possible immune deficit.
Keywords: Bacterial lysate; Immunostimulant; Ismigen®, efficacy, prevention of recurrent upper respiratory tract infections; Upper respiratory tract infections, prevention, recurrent